Comparison Between The Position Of Adopted Children In Islamic Law Inheritance Based On Islamic Law Compilation (KHI) With The Book Of Civil Law - Agil Aladdin; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
This research aims to knowing position adopted child in Islamic Law Compilation with the Book of Civil Law; and Similarities and Differences position adopted children in inheritance of Islamic Law Compilation with the Book of Civil Law; This research method using normative juridical research with comparative approach (comparative). The results were obtained conclusions from Islamic Law Compilation in terms of inheritance, uninterrupted lineage adopted children with biological parents, who turned just the responsibility of the biological parents to the adoptive parents. The adopted child does not become heir of adopted parents. In Gazette No. 129 Of 1917. In Article 5 through Article 15. The position adopted child found in Article 12 to equate a child with a legitimate child of the marriage of the lift. According to the Civil Law for the adopted child the same as for biological children. While in KHI adopted children get as much as 1/3 of the estate left by his adoptive parents (Article 209 KHI) exception has been assigned the consent of all the heirs.Keywords: Heritage; Adopted; Testament.